Knowledge, Motivation, and Attitudes of Truck Drivers Performing First Aid - Arief, Ana Dwiyana; Soeharto, Setyawati; Suryanto, Suryanto (Media Kesehatan Masyarakat Indonesia, 2021)
Cross-provincial lanes in Majalengka are often passed by truck drivers, and they often encounter accidents in which their help is required. The aim of this study was to determine the direct and indirect effects of truck drivers’ knowledge, motivation, and attitudes when performing first aid and the most dominant influencing factors. The research followed a cross-sectional design, and 55 respondents were chosen using total sampling. Partial Least Squares Structural Equation Modeling was used for data analysis. In relation to the practice of first aid, the direct effect of knowledge was found to be significant (p=0.001), motivation was insignificant (p=0.341), and attitude was significant (p=0.017). The indirect effects resulting from the intervention of knowledge motivation was found to be insignificant in the practice of first aid (tstatistic 0.530 < ttable 1.96), and attitude was also not significant (tstatistic 0.758 < ttable 1.96). Attitude was found to be the most dominant factor.